Effects of hydraulic loading rate and organic load on the performance of a pilot-scale hybrid VF-HF constructed wetland in treating secondary effluent - Bang, Woo Hyuck; Jung, Yeonsung; Park, Ji Won; Lee, Seunghak; Maeng, Sung Kyu (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This study evaluated the performance of a pilot-scale hybrid constructed wetland system for secondary effluent and investigated bulk organic matter characteristics. The hybrid constructed wetland consisted of a vertical-flow (VF) bed followed by a horizontal-flow (HF) bed. We also investigated the effects of hydraulic loading rates and influent organic load on the performance of the pilot-scale VF-HF hybrid constructed wetland. The results showed a high removal efficiency for suspended solids (>95%) and organic matter as determined by total organic carbon (>98.5%) and dissolved organic carbon (>70%), but no significant change in nitrogen removal was observed. The wetland treatment efficiency for suspended solids and organic matter showed a good buffer capacity even when hydraulic loading rates increased from 750 to 1500 L m(-2) d(-1) and 500-1000 L m(-2) d(-1) during the VF and HF stages, respectively. Moreover, there was no significant change in the performance when influent organic load increased eightfold. Fluorescence excitation-emission matrix and liquid chromatography-organic carbon detection (LC-OCD) were used to investigate the dissolved organic matter characteristics in the hybrid VF-HF constructed wetland. Fluorescence excitation-emission matrix spectroscopy showed that both protein and humic-like substances did not significantly change in the effluent when hydraulic loading rates and organic load increased by two- and eight-fold, respectively. Biopolymers determined using LC-OCD were effectively removed via the VF and HF stage wetlands, indicating the occurrence of biodegradation. Fluorescence excitation-emission matrix spectroscopy and LC-OCD provided the fate of dissolved organic matter characteristics in the hybrid VF-HF constructed wetland. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: WASTE-WATER TREATMENT; NITROGEN REMOVAL; MATTER; CHROMATOGRAPHY; WASTEWATERS; EXCITATION; QUALITY; CARBON